Réponses

Meilleure réponse !
2013-02-10T18:44:41+01:00
I^2 = (2v3 + 5)^2 donc (2v3)^2 + 2x2v3x5 + 5^2 = 4x3 + 20v3 + 25 = 37 + 20v3 J^2 = (2v3 - 5)^2 = (2v3)^2 - 2x2v3x5 + 5^2 = 12 - 20v3 + 25 = 37 - 20v3 I x J = (2v3 + 5) (2v3 - 5) = (2v3)^2 - 5^2 = 12 - 25 = - 13
2013-02-10T19:00:24+01:00

 

I^2 = (2v3 + 5)^2 

(2v3)^2 + 2x2v3x5 + 5^2 = 4x3 + 20v3 + 25 = 37 + 20v3 J^2 = (2v3 - 5)^2  = (2v3)^2 - 2x2v3x5 + 5^2 = 12 - 20v3 + 25 = 37 - 20v3 I x J = (2v3 + 5) (2v3 - 5) = (2v3)^2 - 5^2  = 12 - 25 = - 13